Gramatika dyadického textu - ŠKVARENINOVÁ, OL’GA (Stylistyka, 2021)
In the text dyadic communication is defined as a specific type of dialogue which is realized interactionally in a concrete, maximal personal situation between two partners who use verbal and nonverbal elements of different semiotical levels. During dyadic communication dyadic text is being produced. Dyadic text has its own typical stylistics formed by verbal and nonverbal elements which represent grarnmar of dyadic text. Ali these elements are divided into the - following - groups: the opening of dyadic communication, the immediate activity, the request for activity, the repetiton of speaker’s statement, the completion of speaker’s statement, the request for clarification, the closing of dyadic communication. Our research shows that in dyadic communication such specific verbal and nonverbal elements are used that we can talk about grarnmar of dyadic text.